2018
DOI: 10.1038/s41598-018-31364-y
|View full text |Cite
|
Sign up to set email alerts
|

The invasiveness of human cervical cancer associated to the function of NaV1.6 channels is mediated by MMP-2 activity

Abstract: Voltage-gated sodium (NaV) channels have been related with cell migration and invasiveness in human cancers. We previously reported the contribution of NaV1.6 channels activity with the invasion capacity of cervical cancer (CeCa) positive to Human Papilloma Virus type 16 (HPV16), which accounts for 50% of all CeCa cases. Here, we show that NaV1.6 gene (SCN8A) overexpression is a general characteristic of CeCa, regardless of the HPV type. In contrast, no differences were observed in NaV1.6 channel expression be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 63 publications
4
43
0
Order By: Relevance
“…Similarly, the mRNA expression of a Nav1.7 splice-variant was ~20-fold higher in cancer than normal tissue [22]. Interestingly, several different Nav1.6 mRNA splice variants (from Exon 18) that would encode non-functional protein were also identified in cervical tissue biopsies [43]. However, the variant 18A encoded a functional protein and its expression correlated with cancer progression, being detected in only 58% of non-cancerous tissues, but 75% of neoplasia, and 100% of cervical cancer samples positive for human papilloma virus type 16.…”
Section: Mrna Level Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the mRNA expression of a Nav1.7 splice-variant was ~20-fold higher in cancer than normal tissue [22]. Interestingly, several different Nav1.6 mRNA splice variants (from Exon 18) that would encode non-functional protein were also identified in cervical tissue biopsies [43]. However, the variant 18A encoded a functional protein and its expression correlated with cancer progression, being detected in only 58% of non-cancerous tissues, but 75% of neoplasia, and 100% of cervical cancer samples positive for human papilloma virus type 16.…”
Section: Mrna Level Studiesmentioning
confidence: 99%
“…However, the variant 18A encoded a functional protein and its expression correlated with cancer progression, being detected in only 58% of non-cancerous tissues, but 75% of neoplasia, and 100% of cervical cancer samples positive for human papilloma virus type 16. Subsequent work thus focused on Nav1.6 as the VGSC driving the invasiveness [43].…”
Section: Mrna Level Studiesmentioning
confidence: 99%
“…High-risk HPV includes HPV 16,18,31 and 33. It can participate in cervical squamous epithelial lesions and cervical cancer to varying degrees [4,5] . Modern studies have shown that the development of cervical squamous epithelial lesions is a multi-step process that develops from normal to inflammatory to tumors, accompanied by multiple genetic changes.…”
mentioning
confidence: 99%
“…Voltage-gated sodium channels (Na V ) are membrane spanning heteromeric complexes, composed of one large pore-forming α subunit (9 isoforms, Na V 1.1–1.9) associated with one or two smaller auxiliary β subunits (4 transmembrane β1-4, and one soluble β1B, isoforms), traditionally considered as features of excitable cells, because of their well-characterized participation in the generation of action potentials. However, it has been recognized that these channels are also expressed, and fully functional, in several carcinoma cells 30 , 44 50 , where they are not associated with cellular excitability but rather to dedifferentiation of epithelial cells 43 , invasive properties and metastatic potencies 37 , 38 , 51 . Several Na V isoforms, mostly Na V 1.5, Na V 1.6 and Na V 1.7 depending on the cancer type 52 , have been shown to be abnormally expressed, but the origin of this dysregulated expression as well as the reasons for the association with a specific cancer tissue have not been identified.…”
Section: Discussionmentioning
confidence: 99%